2004
DOI: 10.1104/pp.103.034082
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structures of Zea mays and Arabidopsis 4-Hydroxyphenylpyruvate Dioxygenase

Abstract: The transformation of 4-hydroxyphenylpyruvate to homogentisate, catalyzed by 4-hydroxyphenylpyruvate dioxygenase (HPPD), plays an important role in degrading aromatic amino acids. As the reaction product homogentisate serves as aromatic precursor for prenylquinone synthesis in plants, the enzyme is an interesting target for herbicides. In this study we report the first x-ray structures of the plant HPPDs of Zea mays and Arabidopsis in their substrate-free form at 2.0 Å and 3.0 Å resolution, respectively. Previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
109
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(116 citation statements)
references
References 56 publications
3
109
1
3
Order By: Relevance
“…15 In the resting form of HPPD the active site iron is six-fold coordinated (2-His-1Glu facial triad and three water molecules) as revealed by X-ray crystal structures (PDB:1SP8,1SP9) and spectroscopic studies. 14,18,19 Results of steady-state kinetics measurements indicated that HPP binds to Fe(II) prior to dioxygen, while CO 2 is the first product released from the active site, similarly to other α-keto acid dependent enzymes. [20][21][22] Respail and co-workers performed QM/MM calculations to test the possible binding modes of HPP in the HPPD active site.…”
Section: Hmsmentioning
confidence: 99%
“…15 In the resting form of HPPD the active site iron is six-fold coordinated (2-His-1Glu facial triad and three water molecules) as revealed by X-ray crystal structures (PDB:1SP8,1SP9) and spectroscopic studies. 14,18,19 Results of steady-state kinetics measurements indicated that HPP binds to Fe(II) prior to dioxygen, while CO 2 is the first product released from the active site, similarly to other α-keto acid dependent enzymes. [20][21][22] Respail and co-workers performed QM/MM calculations to test the possible binding modes of HPP in the HPPD active site.…”
Section: Hmsmentioning
confidence: 99%
“…Early work with organelle fractions attributed most HPPD activity to the chloroplast in spinach (Spinacia oleracea; Fiedler et al, 1982) or Lemna gibba (Löffelhardt and Kindl, 1979). Organelle targeting can be conjectured from the observation that the N-terminal sequence of mature HPPD isolated from maize leaf begins at either Ala-17 (Fritze et al, 2004) or Ala-23 (Yang et al, 2004) with respect to the translated full-length gene. Two HPPD genes identified from EST libraries prepared from cotton tissue were 98.6% identical, each with a 23-amino acid sequence deemed likely to function in chloroplast targeting by analysis with the ChloroP prediction program (Moshiri et al, 2007).…”
mentioning
confidence: 99%
“…HppD has been described in humans (4,44), mouse (9), and rat (10), as well as plants (14,16), fungi (63), and prokaryotes (8,45). There is considerable interest in the HGA catabolic pathway, because HppD in plants is an important herbicide target (5,15,23) and many severe human diseases, like phenylketonuria (18); alkaptonuria (52); tyrosinemias I, II, and III; and hawkinsinuria (48), are associated with enzyme deficiencies in the catabolism of tyrosine.…”
mentioning
confidence: 99%